Beyond the BRICS: Power, Pluralism, and the Future of Global Order. Issue 1 (7th March 2018) - Hurrell, Andrew
Abstract: In the early years of the twenty-first century the narrative of "emerging powers" and "rising powers" seemed to provide a clear and powerful picture of how international relations and global politics were changing. Yet dramatic changes in the global system have led many to conclude that the focus on the BRICS and the obsession with the idea of rising powers reflected a particular moment in time that has now passed. The story line is now about backlash at the core; and, with the exception of China, rising powers have returned to their role as secondary or supporting actors in the drama of global politics. Such a conclusion is profoundly mistaken for three sets of reasons: the continued reality of the post-Western global order; the need to understand nationalist backlash as a global phenomenon; and the imperative of locating and strengthening a new pluralist conception of global order.